Importance of prayer in psychoterapy - Orahovac Ferid (Univerzitetska Misao, 2019)
I have decided to write about the importance of prayer in psychoterapy from many reasons. The first reason is because prayer is today a dominant topic, especially when we talk about the treatment of psychical deseases, where religion and psychoterapy are inseparable.Since I am a theolog, prayer as a religioous ritual is very common to me, and I've noticed it's importance from various religios lectures and from empirical aspect also and, since I use elements of religion to treat people who suffer from various psychosomatic diseases and life difficulties, I was therefore even more interested to approach from a specific scientific aspect and fathom its significance in the psychoterapeutic process. Religion is an aspect of a very big importance in humans lifes. Actually, for most of people, it is one of the main ideas and and a criterion for the establishment of their system of values. Analysing various content (like: books, brochures, encyclopedias, writings), I have found information that scientists have found a certain relationship between science and prayer. This relationship, in these contents is mainly reflected to the importance of prayer in the process of psychotherapy and helping people who have life difficulties and psychological problems. In explaining of this problem, I have used in this work both, scientific and religious literature, in which prayer is treated as a part of religious ritual. I expect that to a certain extent, this work will enlight the nature of the prayer as a religious ritual, but also the relationship between prayer as a specific instrument and psychoterapy techniques, in the process of psychotherapy. I have approached to prayer as a phenomenom and its importance in psychotherapy, from religious and scientific aspect as well. In explaining of this phenomenom, I will bring up the evidence that prayer is uniqely used in treatment, or better said in seeking help of God for solving various difficulties, by the followers of Christianity and by the ones of Islam as well. The followers of Christianity in the way it is explained to christians, and followers of Islam in the way it is prescribed by Islam.